Safety and Efficacy of Direct Angioplasty in Acute Basilar Artery Occlusion Due to Atherosclerosis - Ma, Gaoting; Sun, Xuan; Tong, Xu; Jia, Baixue; Huo, Xiaochuan; Luo, Gang; Wang, Bo; Deng, Yiming; Gao, Feng; Song, Ligang; Ma, Ning; Miao, Zhongrong; et al. (Frontiers in Neurology, 2021)
Background and Purpose: Endovascular treatment (EVT) is one of the promising treatment options in patients with intracranial atherosclerotic disease (ICAD)-related basilar artery occlusion (BAO). In this study, we compared the safety and efficacy of direct angioplasty (DA) with stent-retriever thrombectomy (SRT) with or without rescue treatment in ICAD-related BAO. Methods: We retrospectively evaluated 187 patients who underwent EVT for BAO from January 2012 to July 2018. We identified patients who underwent EVT due to ICAD-related BAO. Patients who accepted SRT with or without rescue treatment were classified into the SRT group. Patients treated with DA with or without stent placement were classified into DA group. Clinical and laboratory findings and outcomes were compared between groups. Results: A total of 108 patients were enrolled, among them 77 underwent SRT and 31 underwent DA; 61 (79.2%) SRT group patients underwent angioplasty with or without stent placement. Compared with patients in the SRT group, those in the DA group experienced a significantly shorter procedure time [60 min (60–120 min) vs. 120 min (60–120 min); p = 0.038] and a lower number of device passes [2 passes (1–2 passes) vs. 3 passes (2–4 passes); p < 0.001]. No significant differences in balloon angioplasty (35.5 vs. 22.1%; p = 0.150), emergent stent placement (64.5 vs. 57.1%; p = 0.481), successful recanalization (93.5 vs. 85.7%; p = 0.340), embolization in distal or new territory (3.2 vs. 9.1%, p = 0.314), and reocclusion (22.6 vs. 9.1%; p = 0.109) among DA and SRT groups were found. Additionally, no differences in symptomatic intracranial hemorrhage incidence [adjusted odds ratio (OR), 0.74; 95% CI, 0.06–9.44; p = 0.815], functional independence (adjusted OR, 1.44; 95% CI, 0.50–4.16; p = 0.497), and mortality rate (adjusted OR, 0.36; 95% CI, 0.06–2.04; p = 0.247) were noted among groups. Conclusions: In certain patients with ICAD-related BAO, DA may shorten procedure time and reduce required device passes compared to SRT. In this study, DA was retrospectively found to be of similar safety and efficacy as SRT.